The Prevalence and Genetic Diversity of Avian Malaria in Wild Birds in the Republic of Korea - Myeongsu Kim; Zun Zun Wut Hmohn; Jae-Ik Han (Animals)
With avian malaria threatening populations of wild birds, this study was conducted to determine its prevalence among wild birds rescued in Jeonbuk state in the Republic of Korea. A total of 1043 wild birds were included in this study from 2017 to 2022. Both quantitative polymerase chain reaction and conventional polymerase chain reaction were used. Plasmodium spp. were detected in 75 of the 1043 (7.19%) wild birds. Plasmodium spp. were detected every year, and their prevalence was significantly higher in winter and winter migratory birds (p < 0.05). The Plasmodium spp. detected in wild birds were confirmed to have 30 different lineages. The most frequently detected species was Plasmodium circumflexum (cytochrome b lineage SW5 and TURDUS1), which is known to prefer cold. In this study, the Plasmodium spp. detected in the Republic of Korea were found to contain a high proportion of species preferring colder climates. This suggested that the monitoring of Plasmodium spp. in the Republic of Korea should be conducted year round, with a focus on monitoring migratory birds coming from colder climates. Ongoing monitoring and research are needed to understand the impact of Plasmodium spp. on wild bird populations.